Free trade in Western Europe - Karlheinz Kleps (Intereconomics, 1972)
Independently of the results of the Summit Conference in Paris it can be said that the entry of Great Britain, Ireland and Denmark into the EEC and the Free Trade Treaties between the enlarged Community and the remaining EFTA countries have decisively advanced the integration process in Western Europe.
Keywords: 330; Foreign Trade